UPAYA PENINGKATAN HASIL BELAJAR SISWA DALAM MATA PELAJARAN IPA MELALUI MODEL PEMBELAJARAN INSIDE-OUTSIDE CIRCLE PADA SISWA KELAS IX.1 SMPN 1 LEMBAH MELINTANG - gustina gustina A (JURNAL MANAJEMEN PENDIDIKAN, 2017)
ABSTRACTBased on the students 'learning outcomes Class IX.1 SMPN 1 Lembah Melintang in science sub subjects Describe the system of excretion in humans and the relationship with health found that students' learning outcomes in subjects IPA sub Describe the system of excretion in humans and the relationship with health is still very low. The average student learning outcomes are still below the KKM. The purpose of this study is to describe and obtain information about Improvement Efforts of student learning outcomes in sub science subjects Describe the system of excretion in humans and health relations through the Inside-Outside Circle Learning Model in Class IX.1 SMPN 1 Lembah Melintang Pasaman Barat Regency. This study is a classroom action research. The research procedure in this research includes planning, action, observation and reflection. This study consists of two cycles with four meetings. The subjects consisted of 32 students of Class IX.1 SMPN 1 Lembah Melintang. The data were collected using observation sheet and daily test. Data were analyzed using percentages. Based on the results of research and discussion that have been proposed, it can be concluded that the Learning Model Inside-Outside Circle can improve student learning outcomes in sub science subjects Describe the system of excretion in humans and health relationships in SMP N 1 Lembah Melintang. Student learning outcomes from cycle I to cycle II. Student learning outcomes in cycle I was 62.22 (Enough) increased to 86.59 (Good) with an increase of 24.38%.Keywords: Learning Outcomes, Science, Learning Model Inside-Outside Circle